The Effect of MgO on the Viscosity of the CaO-SiO2-20 wt%Al2O3-MgO Slag System - Kim, Hyuk; Kim, Wan Ho; Sohn, Il; Min, Dong Joon (Steel research international, 2010)
The viscosities of CaO‐SiO2‐20 wt%Al2O3‐MgO slags (CaO/SiO2 = 1.0–1.2, wt%MgO = 5–13) were measured to estimate the effect of MgO on the viscous behaviour at elevated temperatures. The slag viscosity at 1773 K decreased with increasing MgO contents, which was typical of a basic oxide component at relatively low basicity (CaO/SiO2) of 1.0. The FT‐IR spectroscopic analysis of the slag structure seems to verify this behaviour. However, an unexpected contradiction with the temperature dependence was observed above 10 wt%MgO and above CaO/SiO2 of 1.2. Although the apparent activation energy was expected to decrease with additions of the basic oxide component MgO, the apparent activation energy increased. This unexpected behaviour seems to be related to the change in the primary phase field correlating to the phase diagram corresponding to the slag composition. Therefore, in order to understand the viscosity at both high Al2O3 and MgO, not only should the typical depolymerization of the slag structure with high MgO content be considered but also the primary phases of which the molten slag originates.